This I Believe - Eristoff, Anne (Tufts Archival Research Center, 2006)
Anne Eristoff does not believe the concept of Hell should be a motivating factor for good behavior but rather believes that incentive should come from wanting to be a part of the natural harmony of the world through goodness, truth and beauty.